An Assessment of the Physical Fitness of Senior High School Learners: Basis for the Development of a Home-Based Physical Fitness Plan - Dominado, Noel L. (Future Science / FSH-PH Publications, 2023)
This study was conducted to determine the Physical Fitness Levels of Learners during the Lockdown Period: Basis for the Development of a Home-Based Physical Fitness Plan: To achieve the purpose of the study, the descriptive research design was used. Seventy-six (76) eleventh graders Health Optimizing Physical Education Accountancy, Business Management learners of Senior High School in Magalang Stand Alone 2 in the School Year 2020-2021 served as respondents of the study. The result revealed that body mass index marked a case of overweight and underweight, the respondents’ health-related fitness show above normal, needs improvement cardiovascular endurance, fair and needs improvement muscular strength. However, some are fair and need improvement in hamstring flexibility, and needs improvement in left shoulder girdle flexibility. Furthermore, the skill-related fitness of the respondents shows poor, fair, and needs improvement agility. Furthermore, poor and needs improvement balance, fair and needs improvement coordination. However, needs improvement and developing performance speed. Lastly, needs improvement in the leg, while needs improvement in reaction time. It is suggested the development of effective preventive strategies for all unfit students who are at high risk of being underweight and overweight and the design of programs that will enhance the fitness of students’ health and skill-related fitness.